Optimalisasi Penanaman Budaya Religius dalam Membentuk Karakter Peserta Didik yang Berintegritas di SDI Miftahul Huda Plosokandang Kedungwaru Tulungagung - Nik Haryanti; Danar Nanda Rachmawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to contribute to improving the quality of education in Indonesia by examining how the instillation of religious culture can shape students’ character with integrity, enhance their awareness and practice of religious values, and serve as a reference for educators and policymakers in developing effective educational programs. The research specifically focuses on optimizing the instillation of religious culture in shaping the character of students at SDI Miftahul Huda Plosokandang, Kedungwaru, Tulungagung. Employing a qualitative-descriptive approach, the study uses purposive sampling to collect data through interviews, observations, and documentation. The data were analyzed using techniques of condensation, display, and drawing conclusions. The results reveal that the optimization of religious culture at SDI Miftahul Huda is implemented through various school-integrated activities, such as reciting prayers before and after lessons, performing congregational prayers, engaging in tadarus Al-Qur’an, and celebrating Islamic holidays. These activities go beyond religious routines, functioning as tools to develop students’ integrity, including honesty, responsibility, discipline, and mutual respect. The active role of teachers, school leaders, and a supportive school environment fosters a religious atmosphere that encourages students to internalize spiritual values in daily life. Consequently, the instillation of religious culture at SDI Miftahul Huda effectively contributes to shaping students with noble character and strong integrity.